Investigation into Etna’s summit effusive activity by correlating satellite-derived erupted volumes and strain response - Bonaccorso, A.; Carleo, L.; Cappello, A.; Aloisi, M.; Bilotta, G.; Cannavò, F.; Currenti, G.; Sicali, A.; Ganci, G. (Frontiers in Earth Science, 2025)
Over the past 20 years, Etna’s South-East Crater (SEC) has been the most active of the summit craters, producing more than 100 lava fountains and several effusive eruptions. The latter, lasting from days (effusive pulses) to tens of days (more prolonged effusive phases), occur frequently and thus require accurate volume estimation. Such eruptions usually produce small deformations (≤1 microstrain) that can be detected by the high-precision borehole dilatometers installed at Etna. Recently, a linear correlation has been found between strain changes and eruption volumes derived from satellite imagery for lava fountains. This study extends the previous findings by incorporating data from the SEVIRI satellite sensor, showing a proportionality between strain and volume also for the effusive pulses. Our study confirms that combining satellite and ground-based data enables real-time volcanic monitoring and volume estimation. This enhances the understanding of eruption dynamics and mass balance efficiency, therefore also contributing to the correct and effective communication of volcanic hazards.